Study of transport behavior for Fe-doping La0.67Ca0.33MnO3 perovskite manganese - 崔玉建 葛洪良 韩雁冰 贾广强 王新燕 曹义刚 张金仓 (Journal of Zhejiang University. A. Science, 2004)
Systematic studies of the transport properties of La0.67Ca0.33Mn1-xFexO3 (x=0-0.3) systems showed that with increasing Fe-doping content x the resistance increases and the insulator-metal transition temperature moves to lower temperature. For small doping content, the transport property satisfies metal transport behavior below the transition temperature, and above the transition temperature it satisfies the small polaron model. This behavior can be explained by Fe^3+ doping, which easily forms Fe^3+ -O^2- -Mn^4+ channel, suppressing the double exchange Mn^3+ -O^2- -Mn^4+ channel and enhancing the spin scattering of Mn ions induced by antiferromagnetic clusters of Fe ions.